Localization of trypsin-like protease in postmortem tissue of white shrimp (Litopenaeus vannamei) and its effect in muscle softening. (30th August 2019) - Peng, Yuanhuai; Chen, Shiyan; Ji, Hongwu; Liu, Shucheng
Highlights: The trypsin-like protease was extracted, purified and labeled with FITC. The migration of FITC-trypsin-like protease injected into the hepatopancreas represented the moving of its endogenous trypsin-like protease. FITC-trypsin-like protease which was injected into the hepatopancreas of white shrimp was localized and tracked during the postmortem storage. The results showed that FITC-trypsin-like protease can migrated into tissue of the postmortem muscle. The experimental results demonstrated that trypsin-like protease was responsible for softening of postmortem muscle. Abstract: Fluorescein-isothiocyanate (FITC) labeled trypsin-like protease was prepared and injected into the hepatopancreas of white shrimp. Different segments of the injected shrimp were analyzed with a fluorescence microscope during storage. FITC-trypsin-like protease can be detected in the first segment of shrimp muscle at day 4, while it cannot be observed in the second segment until day 6. The results showed that trypsin-like protease can migrate from hepatopancreas to the tail portion. Texture profile analysis showed that soybean trypsin inhibitor retarded the softening of the shrimp muscle. The rheological results revealed that the content of myosin heavy chain (MHC) in shrimp muscle was decreased with the extended storage time. Proteomics analysis displayed that trypsin-like protease accelerated the metabolism of postmortem muscle. It can be concluded that trypsin-like protease migrated from the hepatopancreas to the muscle tissue, degraded myofibrillar protein, deteriorated the muscle texture, and eventually leaded to the softening of white shrimp.